Juxtaposing Time : an Anthropology of Multiple Temporalities in Morocco - Leila Abu-Shams; Araceli González-Vázquez (Revue des Mondes Musulmans et de la Méditerranée)
Three different calendars coexist in contemporary Morocco: Gregorian, Muslim and Agrarian. Each governs ritual times, feast days, events and daily life activities. The coexistence of these calendars both layers and juxtaposes measures of time. Time and temporality offer a unique entry point for understanding various aspects of the Moroccan lifecycle, including the social and economic contexts. In this article, we analyse the way in which different temporal regimes coexist and we explore the historical and power dynamics that shape the relevance of each. In our paper we evaluate the role of social discourse and practice in maintaining the stability of a regime of heterogeneous and multiple temporalities. Given the multiplicity of time markers, time frameworks and calendars, an important aspect is time-telling and time-shifting. Drawing on ethnographic examples from Morocco, we will shed light on the social and cultural understanding of time.